Politics : A very short Introduction - Minogue, Kenneth (New York Oxford University Press, 2000)
Discusses the development of politics from the ancient world to the twentieth century. The author prompts the reader to consider why political systems evolve, how politics offers both power and order in the society, whether democracy is always a good thing, and what future politics may have in the twenty-first century.
Include Index
Keywords: Political science -- Politiek